Comparison between the competitive activities and cooperative learning effects on selected football skills of students - Amir, S.; Behrouz, A.; Parvaneh, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
The aim of this research was to compare the competitive activities and cooperative learning effects on selected football skills of students. To this end, 32 male youths (age 13 to 15 yrs) were randomly selected and divided into two groups. The subjects participated in retention and transfer tests after pretest and 8 sessions of practice which included dribbling and passing. Analysis of the data applied an independent t- test and a level of significance at p<0.01 level was utilized. The results showed that the cooperative learning method in which the subjects attempted to achieve the main goals in small regular and heterogeneous groups (of skill and ability level) was significantly more effective than when considering competitive activities in skill levels. The outcomes of this research suggests that to learn and to develop an individuals skill in different sports, in this case in football, with the advantages of using cooperative learning, the coaches will be able to program their teaching, learning and development of different skills in different sports more appropriately.